Novel Whey Fermented Beverage Enriched with a Mixture of Juice Concentrates: Evaluation of Antimicrobial, Antioxidant, and Angiotensin I Converting Enzyme Inhibitory (ACE) Activities Before and After Simulated Gastrointestinal Digestion - Paschalia Kotsaki; Maria Aspri; Photis Papademas (Microorganisms)
This study explored the development of a novel whey-based fermented beverage enriched with juice concentrates and health-promoting ingredients, emphasizing its bioactive properties. The formulation included whey protein isolate (5%), juice concentrates (10% apple, raspberry, and cranberry), and inulin (4%). Fermentation was carried out with the following strains: Lacticaseibacillus rhamnosus (LGG), Lacticaseibacillus casei (431), and Lactobacillus helveticus (R0052) at 2%. Antimicrobial activity was evaluated against pathogens including Listeria monocytogenes (strains 33423 and 33413), Staphylococcus aureus (113 and Newman), Bacillus cereus (DPC 6089), Escherichia coli (NCTC 9001), and Salmonella Enteritidis (NCTC 6676). Antioxidant capacity was measured using 2,2-Diphenyl-1-picrylhydrazylradical (DPPH) and Ferric Reducing Antioxidant Power (FRAP) assays, and angiotensin-converting enzyme (ACE) inhibitory activity was assessed. All bioactivities were found to be high in fermented whey beverage and a further significant increase was observed after simulated gastrointestinal digestion. This fruit-flavored whey beverage demonstrated notable antimicrobial and antioxidant activities, highlighting its potential for functional food applications aimed at combating harmful bacteria and oxidative stress.